Al-Ghazāli's Perspective Values of Education: A Study Of The Book Of Ayyuhā Al Walad - AL AYYUBI, HUDZAIFAH (IJIT: Indonesian Journal of Islamic Teaching, 2020)
The phenomenon of psychological disruption of students in distance learning or online interferes with the effectiveness of learning objectives and can also erode everyone's moral values. These moral values cannot be applied perfectly as in the previous average period. The Ayyuhā al-Walad book is a book that presents moral values and was written by a reforming scholar figure as well as a Muslim philosopher with Sunni aqidah. These moral values are still relevant to the present and in line with the 2003 National Education System Law mandate. This paper aims to reveal these important values to form a Muslim person who approaches perfection by internalizing the values of moral education—these values, namely: Keeping Time, Tazkiyat al-Nafs, Study, and Tawakal.